Small bowel GIST with hemorrhagic shock diagnosed by capsule endoscopy and double‐balloon endoscopy, angiography‐guided hemostasis, and laparoscopic‐assisted resection. Issue 5 (15th May 2021) - Kogo, Hideki; Shimanuki, Kimiyoshi; Iwao, Toshiyasu; Yoshida, Hiroshi
Abstract: Small bowel tumors presenting with hemorrhagic shock require urgent treatment with angiographic embolization to achieve hemostasis. Capsule endoscopy and double‐balloon endoscopy are useful for localizing the tumor, diagnosis, and guiding surgery. Abstract : Small bowel tumors presenting with hemorrhagic shock require urgent treatment with angiographic embolization to achieve hemostasis. Capsule endoscopy and double‐balloon endoscopy are useful for localizing the tumor, diagnosis, and guiding surgery.